De Dilma à Bolsonaro: como a concepção monetária interfere nas políticas públicas - Cabral, Carlos Eduardo Figueiredo (2023)
This paper aims to analyze currency within the capitalist economy and the social impacts during the period from 2011 to 2022. It seeks to demonstrate that money is not merely a facilitator of exchanges. This view of money neutrality is part of the theory called orthodox, which has been and continues to be the adopted model of economic policy in the country and worldwide, with harmful economic and social consequences for the population. In contrast to this theory, the idea that money plays a fundamental role in the system will be presented, as it constitutes the beginning and the outcome of any production, thereby affecting all other economic variables. To support this hypothesis, theoretical resources from authors such as Karl Marx and John Maynard Keynes, among others, will be used